Kepemimpinan dan Akuntabilitas Keuangan di Pemerintah Daerah - Fran Giska Fadhiya Haya; Syukriy Abdullah (Universitas Teuku Umar, 2022)
This literature discusses about the relation between leadership and accountability in local government. Accountability can develop in a transparent and democratic manner as well as freedom in expressing opinions. Therefore, the government must really realize that government and services cannot be separated from the public. The realization of regional financial accountability will be the basis for better governance and the government can provide financial accountability from public funds managed by local governments in order to gain public trust. Regional financial accountability is the responsibility of local governments related to regional financial management for the welfare of the community openly and honestly through the media in the form of presenting financial reports. Leadership is one of the important aspects of the organization, especially in the scope of local government administration. In the recent period, leadership is required to focus more on how the role of leadership in an organization will have a positive impact on the organization. Local governments face great pressure in the implementation of regional autonomy. There are two important institutions in local government, namely DPRD and regional apparatus based on regional regulations. Accountability to local governments will grow when supported by an accountable work environment. The main element of the environment is leadership